Sulfamic Acid-Catalyzed Carbon-Carbon and Carbon-Heteroatom Bond Forming Reactions: An Overview - Brahmachari, Goutam; Banerjee, Bubun (Current Organocatalysis, 2016)
Organocatalytic reactions are now becoming powerful tools in the construction of simple to complex molecular skeletons and this field is growing rapidly with new concepts and designs. During the recent past, sulfamic acid (NH2SO3H) has emerged as an efficient organocatalyst in the formation of both carbon-carbon and carbon-heteroatom bonds, thereby resulting different classes of organic compounds of potential interest. Sulfamic acid is commercially readily available, inexpensive and highly stable, and finds applications as an organocatalyst in organic chemistry. It can catalyze a variety of organic transformations such as many named reactions, protection of different functional groups, one-pot multi-component reactions, condensations, oxidations, ring openings, and the synthesis of various pharmaceutically important heterocyclic compounds. The present review summarizes the latest developments on sulfamic acid-catalyzed organic transformations reported during the last decade with a focus on carbon-carbon and carbonheteroatom bond forming reactions among others.
Keywords: carbon-heteroatom bond